How can we reduce the rate of Violent-Sexual Crimes? An attempt at street design - Yiyao Zhang; Zikai Jin; Shu Zhuang; Shengjie Zhao; Li Ling (PLoS ONE, 2026)
Well-designed streets can foster a harmonious social environment. Street crime rates are closely related to street design, and Violent-Sexual Crime (VSC) is a significant public order concern. While most existing studies address the impact of single environmental factors on street crime, a comprehensive assessment that integrates multiple factors is lacking. As an exploratory study, this research aims to propose and preliminarily validate a multi-factor street design framework aimed at mitigating VSC. First, the Fuzzy Delphi Method (FDM) was used to construct street design guidelines that affect the Violent-Sexual Crime rate, with scoring criteria for street design factors formulated based on the FDM results. Subsequently, Google Street View (GSV) and Semantic Segmentation were utilized to capture the streetscape of the study area. To empirically test this framework, the study conducted an in-depth analysis of fifteen streets, randomly selected from a focused area in London using QGIS. The results indicated a negative correlation between higher environmental scores and lower VSC rates within the studied setting, providing initial, context-specific evidence for the potential utility of the proposed design guidelines. Although findings are primarily applicable to similar urban environments, the methodology offers a transferable model for future research in broader contexts.